The Role of Islamic Banks in Indonesia: A Systematic Literature Review - Yusuf, Mahmud; Komarudin, Parman; Rahmani Abduh, Muhamad; Farhanah, Sri Ana; Nafisah, Hayatun (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2023)
ABSTRACT This study aims to determine the extent to which the role of Islamic banks in the economy in Indonesia. The method used in this research is a systematic literature review which begins with data collection using the Publish or Perish search engine, the assessment is carried out through the websites https://sinta.kemdikbud.go.id/ and https://garuda.kemdikbud.go .id/, to presentation using content analysis techniques, mapping with Vosviewer, and ending with analysis using Biddle's Role Theory. Based on a systematic literature review conducted on 22 Sinta-indexed national journals for the 2017-2022 period, it was found that Islamic banks have an important role in Indonesia, namely as; driving economic growth, assisting the development of MSMEs, assisting the development of the halal industry, helping to tackle the Covid 19 pandemic, and several other roles. Judging from Biddle's Role Theory; 1) Structurally, Islamic banks in Indonesia have played their role as financial institutions through raising investment funds from third parties and channeling financing, 2) Functionally, Islamic banks in Indonesia function as drivers of national and regional economic growth, providers of capital for MSMEs, providers of financing and supporting facilitators for the halal industry, to help tackle Covid 19 through digitalisation of Islamic banking, services that implement health protocols, assistance in procuring Personal Protective Equipment (PPE), assistance with KUR distribution, providing relief for customers affected by the pandemic, and maximizing CSR programs, 3) Interactionally, the role of Islamic banks in Indonesia has not been very effective due to interaction problems in the form of a lack of socialization, promotion, community literacy, and access to Islamic banks which are relatively difficult to reach.